Advancing Mg/Ca analysis of coralline algae as a climate proxy by assessing LA-ICP-OES sampling and coupled Mg/Ca-[delta]18O analysis - Light, Tricia; Williams, Branwen; Halfar, Jochen; Hou, Alicia; Zajacz, Zoltan; Tsay, Alexandra; Adey, Walter (Geochemistry, geophysics, geosystems, 2018)
High-latitude climate reconstructions are essential for discerning anthropogenic climate change from natural climate variability. Since observational high-latitude climate records are rare prior to the satellite era, climate proxies such as the coralline algae Clathromorphum compactum are needed to generate these reconstructions. C. compactum is distributed across the northern high latitudes and documents environmental variability in the magnesium-to-calcium ratio (Mg/Ca) and δ18O composition of its calcite skeleton. Therefore, paired Mg/Ca and δ18O analyses in C. compactum are a promising new tool for reconstructing historic high-latitude climate change. Here a new method for C. compactum Mg/Ca analysis, laser ablation-inductively coupled plasma-optical emission spectroscopy (LA-ICP-OES), was verified through comparisons with parallel Mg/Ca transects using established techniques in a specimen from Labrador, Canada. Next, LA-ICP-OES Mg/Ca analysis in two specimens from Nunavut, Canada, was paired with δ18O analyses. While Mg/Ca data across all specimens captured seasonal sea surface temperature (SST) variability, Mg/Ca values differed in replicate transects within skeleton formed at the same time regardless of technique used. This reduces the effectiveness of C. compactum Mg/Ca as a SST proxy on interannual time scales. Mg/Ca values and δ18O composition differed between the two Nunavut specimens, and only one of them documented local SST, sea ice cover, and sea surface salinity. This indicates that climate archive verification is required for each unique coralline algal specimen. In the specimen from Nunavut verified here, paired Mg/Ca and δ18O analyses produced more robust sea ice cover/sea surface salinity reconstructions than δ18O analyses alone, supporting further development of this proxy system.
Das Delta im Titel ist als griechischer Buchstabe dargestellt, die 18 ist hochgestellt
Gesehen am 06.07.2021